The Influence of Involvement and Commitment on Customer Loyalty with the Mediation of Emotional Engagement on Haidilao Hotpot PTC Surabaya - Angeline Veronica; Jesslyn Verina; Adrie Oktavio (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to examine the effect of engagement and commitment on customer loyalty, with emotional engagement as a mediating variable among Haidilao Hotpot PTC Surabaya customers. The study used a quantitative approach with a survey method by distributing questionnaires to 209 respondents who had visited and made purchases at Haidilao Hotpot PTC Surabaya. Respondents were selected using a purposive sampling technique with the criteria of customers who had consumption experience at the restaurant. The research instrument was constructed using a five-point Likert scale to measure the variables of engagement, commitment, emotional engagement, and customer loyalty. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through the SmartPLS application. The results showed that commitment had a positive and significant effect on emotional engagement and customer loyalty. Emotional engagement was also shown to significantly increase customer loyalty. Conversely, engagement showed a significant negative effect on customer loyalty and had no significant effect on emotional engagement. In addition, emotional engagement successfully mediated the relationship between commitment and customer loyalty, but was unable to mediate the relationship between engagement and customer loyalty. These findings emphasize the importance of relational and emotional aspects in building customer loyalty in the restaurant industry